Pengaruh Self-Efficacy Terhadap Self-Acceptance Mahasiswa Pendidikan Kesejahteraan Keluarga - Adelia Nasya Andani; Maya Oktaviani; Mulyati Mulyati (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2023)
This study aims to determine self-efficacy's effect on the students' self-acceptance of the Family Welfare Education Study Program at Universitas Negeri Jakarta. The study uses the associative quantitative method on 148 active students from the 2019-2021 class (129 female and 19 male). The study was conducted at Universitas Negeri Jakarta from April to October 2022. The self-efficacy was measured using a general self-efficacy scale. Whereas self-acceptance was measured using an unconditional self-acceptance questionnaire. The results showed that: (1) students had a high level of self-efficacy, (2) students had a high level of self-acceptance, (3) there was a significant effect of self-efficacy on students' self-acceptance, and (4) 69% of the variation of the self-acceptance variable can be explained through the variation of the self-efficacy variable. Students need to have confidence in their abilities, effort, and perseverance to solve the problems they face to have high self-acceptance. The findings of this study, it is.Keywords - Self-efficacy, Self-acceptance, College student.